FACTORS RELATING TO THE PERFORMANCE OF HEALTH WORKERS IN ABELI CITY HEALTH CENTER, KENDARI CITY: Performance of Health Workers - Muhammad Ikhsan Akbar; Wa Ode Nova Noviyanti Rachman; Sartini Risky MS (STIKes Mandala Waluya Kendari, 2020)
Background: Public health center is the spearhead for improving the welfare of the community in the health sector. The health worker's skill needs to be optimized and can be seen from the results of their work, in the form of mastery of science and technology, as well as skills in implementing and providing health services. This is evident from the last three months' report on community visits, namely, in December 2016 the number of visits was 138 people, in January 2017 fell to 108 visits and in February 2017 dropped dramatically 93 visits. The purpose of this study was to determine the relationship of discipline, motivation, and training with the performance of health workers in the Abeli ??Community Health center. Methods: This type of research is quantitative with a cross-sectional study design. The population in this study was 42 people with a total sampling technique with a total sample of 42 people. The analytical method uses the Chi-Square statistical test and the Phi coefficient (?). Results: Based on the results of the study, there is a strong relationship between discipline and the performance of health workers with a value of X2 Calculation = 17,835 and a phi-efficiency test (?) = 0.651. There is a strong relationship between motivation and the performance of health workers with a value of X2 Calculation = 16,481 and the tested coefficient phi (?) = 0.626. There is a moderate correlation between training and health worker performance with X2 Calculation value = 10.299 and the phi coefficient test (?) = 0.495. Conclusion: For the health, institutions are suggested to increase the health worker's knowledge by increasing towards more discipline, high motivation, and more training in order. Eventually, the quality of human resources and health organizational performance will increase.